Can Short-Term Capital Controls Promote Capital Inflows? - Cordella, Tito (IMF Working Papers; Working Paper ;, 1998)
In an economy a la Diamond and Dybvig (1983), we present an example in which foreign lenders find it profitable to invest in an emerging market if, and only if, the emerging market government imposes taxes on short-term capital inflows. This implies that capital controls that are effective in reducing the vulnerability of emerging markets to financial crises may increase the volume of capital inflows.